THE IMPORTANCE OF MODERN TECHNOLOGY FOR TEACHING ENGLISH TO PRIMARY SCHOOL PUPILS - Hojikurbonova, Mashhura Shermat kizi; Khasanova, Yulduz Mukhtor kizi (Innovative Development in Educational Activities, 2024)
The purpose of this research is to determine the importance of using modern technologies in teaching English to primary school students. In order to facilitate the process of learning for young learners and provide them with more convenient opportunities, it is necessary to first investigate the environment in which they learn quickly and the factors that help them achieve quicker and more effective results in learning English. Conducting research related to this topic, alongside gathering information from other relevant studies, demonstrates that integrating modern technologies in teaching enhances students’ understanding and retention of new topics, significantly boosts their interest and enthusiasm for learning English and attending classes. The aim of using qualitative methods in this research is to identify how it influences primary school students. In this scenario, a class consisting of 15 students was divided into two groups based on a topic relevant to their grade level, and two different types of lessons were conducted. In the first lesson, traditional methods were used without any modern technologies. English language cartoons, videos, podcasts, and audios help students immerse themselves in the English atmosphere and pay closer attention in class. In conclusion, modern technologies facilitate students’ learning processes, make learning the English language easier, and transform this process into an engaging experience.